Correlated isotopic and chemical evidence for condensation origins of olivine in comet 81P/Wild 2 and in AOAs from CV and CO chondrites. (15th January 2021) - Fukuda, Kohei; Brownlee, Donald E.; Joswiak, David J.; Tenner, Travis J.; Kimura, Makoto; Kita, Noriko T.
Abstract: Magnesium stable isotope ratios and minor element abundances of five olivine particles from comet 81P/Wild 2 were examined by secondary ion mass spectrometry (SIMS). Wild 2 olivine particles exhibit only small variations in δ 25 Mg values from –1.0 +0.4 /–0.5 ‰ to 0.6 +0.5 /–0.6 ‰ (2σ). This variation can be simply explained by mass-dependent fractionation from Mg isotopic compositions of the Earth and bulk meteorites, suggesting that Wild 2 olivine particles formed in the chondritic reservoir with respect to Mg isotope compositions. We also determined minor element abundances, and O and Mg isotope ratios of olivine grains in amoeboid olivine aggregates (AOAs) from Kaba (CV3.1) and DOM 08006 (CO3.01) carbonaceous chondrites. Our new SIMS minor element data reveal uniform, low FeO contents of ∼0.05 wt% among AOA olivines from DOM 08006, suggesting that AOAs formed at more reducing environments in the solar nebula than previously thought. Furthermore, the SIMS-derived FeO contents of the AOA olivines are consistently lower than those obtained by electron microprobe analyses (∼1 wt% FeO), indicating possible fluorescence from surrounding matrix materials and/or Fe, Ni-metals in AOAs during electron microprobe analyses. For Mg isotopes, AOA olivines show more negative mass-dependent fractionation (–3.8 ± 0.5‰ ≤ δ 25 Mg ≤ –0.2 ± 0.3‰; 2σ) relative to Wild 2 olivines. Further, these Mg isotope variations are correlated with their host AOA textures. Large negative Mg isotope fractionations in olivine are often observed in pore-rich AOAs, while those in compact AOAs tend to have near-chondritic Mg isotopic compositions. These observations indicate that pore-rich AOAs preserved their gas–solid condensation histories, while compact AOAs experienced thermal processing in the solar nebula after their condensation and aggregation. Importantly, one 16 O-rich Wild 2 LIME olivine particle (T77/F50) shows negative Mg isotope fractionation (δ 25 Mg = –0.8 ± 0.4‰, δ 26 Mg = –1.4 ± 0.9‰; 2σ) relative to bulk chondrites. Minor element abundances of T77/F50 are in excellent agreement with those of olivines from pore-rich AOAs in DOM 08006. The observed similarity in O and Mg isotopes, and minor element abundances suggest that T77/F50 formed in an environment similar to AOAs, probably near the proto-Sun, and then was transported to the Kuiper belt, where comet 81P/Wild 2 likely accreted.